Targeting Aging: Lessons Learned From Immunometabolism and Cellular Senescence - Martin, Dominique E.; Torrance, Blake L.; Haynes, Laura; Bartley, Jenna M. (Frontiers in Immunology, 2021)
It is well known that aging is associated with dysregulated metabolism. This is seen both in terms of systemic metabolism, as well as at the cellular level with clear mitochondrial dysfunction. More recently, the importance of cellular metabolism in immune cells, or immunometabolism, has been highlighted as a major modifier of immune cell function. Indeed, T cell activation, differentiation, and effector function partly depend on alterations in metabolic pathways with different cell types and functionality favoring either glycolysis or oxidative phosphorylation. While immune system dysfunction with aging is well described, what remains less elucidated is how the integral networks that control immune cell metabolism are specifically affected by age. In recent years, this significant gap has been identified and work has begun to investigate the various ways immunometabolism could be impacted by both chronological age and age-associated symptoms, such as the systemic accumulation of senescent cells. Here, in this mini-review, we will examine immunometabolism with a focus on T cells, aging, and interventions, such as mTOR modulators and senolytics. This review also covers a timely perspective on how immunometabolism may be an ideal target for immunomodulation with aging.